ChemInform Abstract: Cascade Nitrosation and Addition—Elimination of Nitroacetanilides for the Highly Efficient Synthesis of 1, 4, 2, 5‐Dioxadiazine Derivatives. Issue 47 (6th November 2014) - Mo, Shanyan; Huang, Peipei; Xu, Jiaxi
Abstract The key intermediate is the aci‐nitroso species, which is stabilized by the conjugated aryl moiety.